Pendidikan agama Islam di era post-truth: Upaya penguatan karakter siswa melalui literasi digital - Maysurah, Maysurah; Maimun, Maimun; Suyyirah, Suyyirah; Aini, Nur (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2025)
Strengthening character through digital literacy is an effort to shape students' attitudes and behavior to be wise, critical, and responsible in using digital media. This study aims to describe the efforts of Islamic religious education teachers in strengthening student character through digital literacy at SMA NU Nurul Hajar Dungkek Sumenep. This type of research is a case study using qualitative research methods. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. The results indicate that Islamic religious education teachers play a strategic efforts in instilling Islamic values and etiquette in the use of digital technology. Through the integration of Syed Naquib Al-Attas's concept of ta'dib, digital literacy is understood not only as technological skills but also as the process of developing digital etiquette and morality. Efforts to strengthen digital literacy based on Islamic values help students become wise media users, critical of information, and imbued with Islamic morals in facing the challenges of the post-truth era.